Proteomics of ionomycin‐induced ascidian sperm reaction: Released and exposed sperm proteins in the ascidian Ciona intestinalis. Issue 23 (25th September 2015) - Nakazawa, Shiori; Shirae‐Kurabayashi, Maki; Otsuka, Kei; Sawada, Hitoshi
Abstract : Sperm proteins mediating sperm–egg interaction should be exhibited on the sperm surface, or exposed or released when sperm approach an egg. In ascidians (protochordates), sperm undergo a sperm reaction, characterized by enhanced sperm motility and mitochondrial swelling and shedding on contact with the vitelline coat (VC) or by treatment with Ca 2+ ionophore. Here, proteomic analysis was conducted on sperm exudates and sperm surface proteins using ionomycin‐induced sperm reaction and cell‐impermeable labeling in Ciona intestinalis type A ( C. robusta ). In the exudate from sperm treated with ionomycin, membrane proteins including a possible VC receptor CiUrabin were abundant, indicating the release of membranous compartments during sperm reaction. Among the surface proteins XP_009859314.1 (uncharacterized protein exhibiting homology to HrTTSP‐1) was most abundant before the sperm reaction, but XP_004227079.1 (unknown Ig superfamily protein) appears to be most abundantly exposed by the sperm reaction. Moreover, proteins containing a notable set of domains, astacin‐like metalloprotease domain and thrombospondin type 1 repeat(s), were found in this fraction. Possible roles in fertilization as well as localizations and behaviors of these proteins are discussed.